THE EFFECTIVENESS OF COOPERATION AND STUDENT’S SELF CONFIDENCE THROUGH THE IMPLEMENTATION OF COOPERATIVE LEARNING MODEL TYPE NUMBER HEAD TOGETHER (NHT) ON EQUILIBRIUM SHIFTMENT MATTER IN SMAN 1 SIDOARJO (Universitas Negeri Surabaya, 2018)
This study aims to determine the implementation of learning, cooperation and student’s self confidence after the implementation of cooperative learning model type NHT on equilibrium shiftment matter. This research type is Pra Experiment (pre experiment design) and research design is One-Group Pretest-Postest Design. Target of this research is student of class XI MIPA 6 SMAN 1 Sidoarjo. The instrument used are an observation sheet of cooperative learning model type NHT, an observation sheet of cooperation and self confidence questionnair. This research showed that (1) the average percentage of the implementation cooperative learning model type NHT on introduction was 91.67%, phase 1 was 79.16%, phase 2 was 91.67%, phase 3 which contains stage 1 of NHT was 83.33%, phase 4 which contains stage 2 and stage 3 of NHT was 83.33%, phase 5 which contain stage 4 of NHTwas 95% and phase 6 was 79.16%; (2) the average value of cooperation skills on appreciate the opinions of others indicator was 68.89, remain in groups and tasks indicator was 67.99 and active participant’s indicator was 69.34; (3) the average value of magnitude dimension was 81.25, strenght dimension was 80.08 and generality dimension was 78.13keywords: cooperative learning model type NHT, cooperation skills, students self confidence, equilibrium shiftment